Classification or phylogenetic estimates? - Scotland, R; Carine, M (2000)
[m]3ta is a method that seeks to implement a taxic view of homology. The method is consistent with Patterson's tests for discriminating homology from nonhomology. Contrary to the claims of Kluge and Farris, (1999, Cladistics 15, 205-212), m3ta is not a phenetic method - nor does it necessarily place the basal split in a tree between the phenetically most divergent taxa. [m]3ta does not seek to accurately recover phylogeny but rather it seeks to maximize the information content of taxic homology propositions. [m]3ta is a method of classification in which the unit of analysis is the relation of homology. [m]3ta differs from all phylogenetic methods because the units of analyses in phylogenetic methods, including sca, are transformation series. © 2000 The Willi Hennig Society.